Comparative study of R-phase martensitic transformations in TiNi-based shape memory alloys induced by point defects and precipitates. (May 2017) - Chang, P.C.; Ko, M.L.; Ramachandran, B.; Kuo, Y.K.; Chien, C.; Wu, S.K.
Abstract: We studied the influence of point defects (Fe) and precipitates (Ti3 Ni4 ) on the characteristics of R-phase martensitic transformation by comparing the transport and thermal properties of as-quenched Ti50 Ni46 Fe4 and annealed Ti48.7 Ni51.3 shape memory alloys. Both alloys undergo a weak first-order R-phase transformation with a small thermal hysteresis (less than 7 K) and non-zero transformation strain, suggesting the introduction of point defects and precipitates lead to a stable R-phase in these alloys due to the defects induced local lattice deformations. Furthermore, our study revealed that the transition temperature, transformation width, and transformation strain of the investigated R-phase TiNi-based alloys are strongly affected by the induced defects. As a result, the annealed Ti48.7 Ni51.3 has a higher transition temperature than that of Ti50 Ni46 Fe4, as expected. Highlights: As-quenched Ti50 Ni46 Fe4 and annealed Ti48.7 Ni51.3 alloys display metallic behavior. Both shape memory alloys (SMA) show a p -type thermoelectric transport below 350 K. Both SMA systems undergo a weak first-order R-phase martensitic transformation. The induced defects strongly affect the martensitic transformation characteristics.